2008
DOI: 10.1007/s00726-007-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Theanine, γ-glutamylethylamide, a unique amino acid in tea leaves, modulates neurotransmitter concentrations in the brain striatum interstitium in conscious rats

Abstract: Theanine (c-glutamylethylamide) is one of the major amino acid components in green tea and can pass through the blood-brain barrier. Recent studies suggest that theanine affects the mammalian central nervous system; however, the detailed mechanism remains unclear. In this study, we demonstrated the effect of theanine on neurotransmission in the brain striatum by in vivo brain microdialysis. Theanine injection into the rat brain striatum did not increase the concentration of excitatory neurotransmitters in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Recent studies have reported that theanine has various favorable physiological functions including neuroprotection in transient ischemic neuronal death (Kakuda et al 2000;Yamada et al 2005), relaxing effects under resting conditions (Abdou et al 2006;Lu et al 2004), hypolipidemic functions (Chiang et al 2005), regulation of systemic blood pressure (Yokogoshi et al 1995), suppression of the stimulatory action of caffeine (Nozawa et al 2000), modulation of neurotransmitter (Yamada et al 2009), and protection against hepatic toxicity (Sadzuka et al 2005). Additionally, studies on test rats have shown that repeated, extremely high doses of theanine cause little to no harmful psychological or physical effects (Borzelleca et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have reported that theanine has various favorable physiological functions including neuroprotection in transient ischemic neuronal death (Kakuda et al 2000;Yamada et al 2005), relaxing effects under resting conditions (Abdou et al 2006;Lu et al 2004), hypolipidemic functions (Chiang et al 2005), regulation of systemic blood pressure (Yokogoshi et al 1995), suppression of the stimulatory action of caffeine (Nozawa et al 2000), modulation of neurotransmitter (Yamada et al 2009), and protection against hepatic toxicity (Sadzuka et al 2005). Additionally, studies on test rats have shown that repeated, extremely high doses of theanine cause little to no harmful psychological or physical effects (Borzelleca et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…If ethylamine metabolized from theanine is transported into the brain, it is possible that ethylamine partially participate in the effects of theanine intake. In contrast, in vivo microdialysis experiment indicates that theanine perfusion stimulates dopamine release in the rat striatum (Yamada et al 2009). …”
Section: Discussionmentioning
confidence: 93%
“…It amounts to 1 2% dry weight of green tea, which equates to 25 60 mg per 200 ml serving of liquid tea. Green tea is therefore the major source of dietary L-theanine 37 , which is known to have a calming effect on neurotransmission and mood 38 .…”
Section: Effect Of Mmp Inhibitionmentioning
confidence: 99%
“…It has been reported that inhibitory neurotransmitters, such as glycine and GABA, are released by activating -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid AMPA receptors, which are ionotropic glutamate receptors 38 . Theanine has been found to bind AMPA receptors, but not N-methyl-D-aspartate NMDA receptors 38 .…”
Section: Effect Of Mmp Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation